Studi Kompetensi dan Kepercayaan Diri Mahasiswa Teknik Sipil Untuk Bekerja Di Bidang Konstruksi Bangunan Setelah Melaksanakan PKL - Rahmah Fitriana Sari (LPPM Universitas Negeri Jakarta, 2014)
The objectives of this study to find out the presence of competence and self-confidence of students in Civil Engineering after implementing the practice of fieldwork. The research was conducted at the majoring in civil engineering, Faculty of Engineering, State University of Jakarta in October 2011, the odd semesters (095) academic year 2011 – 2012. This study used a qualitative descriptive method. The population is affordable students of civil engineering who have implementing the practice of fieldwork on semester 095 as many as 130 students. Study sample was 50 students from the existing population was determined using the purposive sampling method. The research instrument is a test to test the competence and questionnaire to test the self-confidence. The scale used is a Gauttman scale and the scale LikertResults of this study is the competence of civil engineering students after implementing the practice of fieldwork to work in the field of building construction has been achieved by 76%. The percentage of each competency indicator variables are cognitive indicators 75%, affective indicator of 94%, and psychomotor indicator 73%. The self-confidence of civil engineering students to work in the field of building construction is also achieved by 77%. The percentage of each self-confidence indicator variable is indicators of self-esteem 74%, indicators of self-afficacy 84%, optimistic indicator of 84%, objective indicator of 94%, and responsibility indicator of 96%.The results of this study was competence and self-confidence of students to work in the field of building construction has been reached on the students after implementing the practice of fieldwork. Competence and self-confidence is the foundation that must be possessed by the student to work in the field of building construction